Bio-impedance spectroscopy for frozen-thaw of bio-samples: Non-contact inductive measurement and finite element (FE) based cell modelling. (May 2020) - Tang, Jiawei; Yin, Wuliang; Lu, Mingyang
Abstract: Biological samples exhibit frequency dependent spectra caused by the dispersion mechanism which describes a phenomenon of dielectric relaxation due to the interaction between electromagnetic field and biological samples at cellular levels. Bio-impedance spectroscopy (BIS) can provide information about the cellular structure, composition and integrity of biological samples. This paper investigates the effect of frozen-thaw process on the bio-impedance of bio-samples through experiments and simulation. In order to overcome the shortcoming of previous research method, contact-electrode method, a non-contact magnetic induction system was built, which contains a custom-designed front-end circuit and a Zurich lock-in amplifier for data acquisition. The system was used to measure the conductivity spectra of potato and fresh loin pork before and after frozen-thaw. The measurement accuracy of the system is 0.01 S/m over a bandwidth of 400 kHz to 6 MHz. In addition, a novel cell-level simulation model was built using finite element method to elucidate the measurement results and provide an explanation based on the structural change of cell membrane. The results from the non-contact magnetic induction measurement agree well with the observations from the microscopic experiments. The non-contact nature of the method is significant as it has the potential for use in real world applications for fast scanning of food products where contact method is not ideal. Highlights: A non-contact system is built to identify the fresh and frozen-thawed food samples rapidly and non-destructively. A novel cell-level simulation model was built using finite element method to elucidate the measurement results. In addition, a microscopic experiment has been carried out to validate the measurement and simulation results.